Aspectos semânticos, morfológicos e morfossintáticos das palavras descritivas Apurinã - CHAGAS, Angela Fabíola Alves (2007)
It presents semantic, morphossyntactic and morphological aspects of the descriptive words of the Apurinã language (Aruákan), that is, words that commonly are translated as adjectives in the European languages. Some of those words receive the mark of pronominal subject (e.g. u-natxitapeka 'she is hungry'); while others receive the objective mark (e.g. ere-ru 'she is beautiful'); and other ones can receive either subjective and objective markers (e.g. ny-pĩkareta eu estou com medo vs. papĩkare-nu eu sou medroso). The first think treated was about the place of the descriptive words in the Apurinã parts of the speech (are they names, are they verbs or do they form an independent class from these?). Using internal evidences of the language, initially we have established a grammatical classification for those words starting from their morphological properties in comparison with the names and verbs in the language, with the purpose of answer these questions. The second think is on the semantic correlates of the descriptive words. Considering the intern division of the Apurinã descriptive words (subjective vs. lenses), we presented the semantic properties associated to each group and, starting from that, we presented an attempt of motivating the sub grouping of descriptive concepts in the language with base in the aspectual notions of transitoriness and permanence. Finally, the described grammatical phenomenon is contextualized inside of the typology of systems of split intransitivity described for other languages (PAYNE: 1997), and the description of their semantic properties is located in relation to the typology of lexical aspects or aktionsarten (COMRIE: 1976, FRAWLEY: 1992).